PENGARUH PELAYANAN, KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI TOKO SNEAKERS ROOM MEDAN - Ayyub Ramadhan; Fauzi Arif Lubis (STKIP Persada Khatulistiwa Sintang, 2022)
With the emergence of many thrift shops that sell used goods, one of which is shoes, some people choose to buy original used shoes instead of buying new original shoes. From theory and several studies show service, product quality, price and promotion on purchasing decisions. For this reason, this study aims to determine the effect of service, product quality, price and promotion on purchasing decisions at the thrift Sneakers Room Medan store. This type of research is quantitative with a survey method. Respondents in this study were 100 consumers of thrift Sneakers Room Medan. The sampling technique used was purposive sampling. The method used in this research is multiple linear regression analysis using SPSS version 16. The results show that there is an effect of service on purchasing decisions, there is an effect of product quality on purchasing decisions, there is an effect of price on purchasing decisions, and there is an influence of promotion on purchasing decisions. Variable service, product quality, price and promotion together have an influence on purchasing decisions.